Working the Spaces of Power - Newman, Janet (Bloomsbury Academic, 2012)
p‰This book highlights the way in which contemporary forms of governance, policy and politics have been reframed by women 'working the spaces of power'. It shows how links between activism and work have generated innovations that have since become 'common sense' forms of policy and practice. /p‰ p‰Janet Newman draws on interviews with a wide variety of women in positions of power, some at the highest levels of government, some who have led major voluntary bodies, others who are entrepreneurs, philanthropists, community activists and campaigners. All of their work has been informed by a range of social movements and activist commitments. Newman uses these interviews to interrogate, develop and challenge existing approaches to understanding social and political change. /p‰